Homomorphic cryptosystems and their applications - Rappe, Dörte K. (Universität Dortmund, 2005)
In this thesis we consider homomorphic cryptosystems and their applications. Homomorphic cryptosystems allow for computations on encrypted data.We prove that the search for an algebraically homomorphic scheme can be reduced to the search of a homomorphic scheme on a special non-abelian group. Furthermore, we focus on a special application: computing with encrypted functions and data, respectively. For this application we develop an improved protocol that is efficient for functions that are computable by polynomial branching programs. Finally, we generalise the elliptic curve Paillier scheme by S. Galbraith in order to construct a threshold version of it. For this threshold scheme we develop several Sigma-protocols. Using these protocols we apply our threshold scheme on multiparty computations, electronic voting and commitment schemes.

Diese Arbeit beschäftigt sich mit homomorphen Kryptosystemen und ihren Anwendungen. Unter homomorphen Kryptosystemen versteht man Verfahren, die Berechnungen auf verschlüsselten Daten zulassen. Es wird bewiesen, dass die Suche nach einem algebraisch homomorphen Verfahren auf die Suche nach einem homomorphen Verfahren auf speziellen nicht-abelschen Gruppen zurückgeführt werden kann. Außerdem wird auf Berechnungen mit verschlüsselten Daten bzw. verschlüsselten Funktionen als Anwendung genauer eingegangen. Für diese wird ein verbessertes Protokoll vorgestellt, dass für Funktionen, die durch polynomielle Branching Pogramme berechnet werden können, effizient ist. Darüber hinaus wird das Elliptic Curve Paillier-Verfahren von S. Galbraith verallgemeinert, in dem eine Schwellwert-Version des Verfahrens konstruiert wird. Für dieses neue Schwellwertverfahren werden Sigma-Protokolle angegeben, die es ermöglichen, das Verfahren auf Wahlverfahren, Commitment-Verfahren und Multiparty-Computation anzuwenden.
Keywords: Homomorphic cryptosystems; encrypted computation; branching programs; elliptic curve Paillier scheme; Homomorphe Kryptosysteme; verschlüsselte Berechnungen; Branching Programme; Elliptic Curve Paillier-Verfahren; 510